Hepcidin-mediated hypoferremia disrupts immune responses to vaccination and infection - Frost, JN; Tan, TK; Abbas, M; Wideman, SK; Bonadonna, M; Stoffel, NU; Wray, K; Kronsteiner, B; Smits, G; Campagna, DR; Duarte, TL; Lopes, JM; et al. (Cell Press, 2020)
Background: How specific nutrients influence adaptive immunity is of broad interest. Iron deficiency is the most common micronutrient deficiency worldwide and imparts a significant burden of global disease; however, its effects on immunity remain unclear.